Algebra in easy steps, Teacher's guide / Edwin L. Stein - Stein, Edwin I. [et. al] (1982)
Overview of student text, agebra in easy steps is an individualized basal text in elementary algebra, It features a wealth of carefully graderd practice material, individualized assignments, a step-by-step approach to problem solving, a comprehensive treatment of the formula, a complete testing program, and an abundance of interesting applications from informal geometry, aritmetic, commerce, science, industry, and aviation showwing practical value of algebraic principles and skills. All these materials are so organized thet diagnostic and prescriptive techniques may easily de used.